1999
DOI: 10.1177/073490419901700102
|View full text |Cite
|
Sign up to set email alerts
|

Potential Health Hazards from Burning Aircraft Composites

Abstract: Burning of polymer matrix composites in postcrash aircraft fires generates a complex mixture of combustion products comprised of gases, organic vapors, and particulate matter including airborne carbon fibers. There is concern among the fire fighting, investigative, and mishap response communities that an unusual health hazard is posed by this combination of combustion products. This paper presents an overview of the nature and potential hazards of acute exposure to airborne carbon fibers from fire and explosio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 8 publications
0
27
0
1
Order By: Relevance
“…Fibers inside the smoke plume occur in different forms, ranging from single filaments to fragments that can contain up to several hundred filaments bound together by char or resin. An analysis of graphite fibers collected in the smoke plume of burning graphite/epoxy composites has revealed that the mean fiber diameter is under 7 m, which is within the respiratory range [28]. Figure 4 shows a distribution plot giving the range of fiber diameters collected from the smoke of a graphite/epoxy laminate.…”
Section: A Fibers In Smokementioning
confidence: 82%
See 3 more Smart Citations
“…Fibers inside the smoke plume occur in different forms, ranging from single filaments to fragments that can contain up to several hundred filaments bound together by char or resin. An analysis of graphite fibers collected in the smoke plume of burning graphite/epoxy composites has revealed that the mean fiber diameter is under 7 m, which is within the respiratory range [28]. Figure 4 shows a distribution plot giving the range of fiber diameters collected from the smoke of a graphite/epoxy laminate.…”
Section: A Fibers In Smokementioning
confidence: 82%
“…The toxic potency generally increases with the fiber concentration and when the fiber particle size is within a narrow range (usually in the micron size range). Several studies have measured the concentration and sizes of fiber particles in the smoke plume of burning composite materials, and the key findings have been reviewed by Gandhi et al [28]. The studies measured the amount and size of fibers released from burning graphite-epoxy composites [63][64][65][66][67][68].…”
Section: A Fibers In Smokementioning
confidence: 99%
See 2 more Smart Citations
“…This is a desirable test for composite materials because the release of ultra-small fragments of the reinforcing fibres during combustion could be a health concern [34,35]. The soot yield can be determined by placing a filter sampler into the exhaust stream of the cone calorimeter.…”
Section: (A)mentioning
confidence: 99%